Effectiveness of Tactical Approach in Volleyball Learning in Higher Education: A Case Study of Dehasen University - Ertanto, Dody; Sumantri, Ajis (Indonesian Journal of Sport Management, 2024)
The tactical approach in sports education has enhanced comprehension of game strategies and technical abilities. Nonetheless, its efficacy regarding volleyball teaching in higher education, particularly at Dehasen University, has not been extensively examined. This study seeks to evaluate the effectiveness of the tactical method in enhancing the comprehension of tactics and volleyball abilities among Physical Education students. The research employed an experimental design utilizing a quasi-experimental methodology, comprising 40 students allocated into experimental and control groups—the research tools comprised skill assessments and observations of tactical comprehension. The findings indicated a substantial enhancement in the experimental group relative to the control group, with an average rise of 25% in playing ability scores (p < 0.05) and a 30% increase in tactical comprehension (p < 0.05). In conclusion, the tactical approach improves students' volleyball skills and understanding. The researcher advocates for incorporating a tactical approach into the volleyball curriculum in higher education, supplemented by training for instructors to enhance the execution of this method.